Blacks in Gold Rush California - Lapp, Rudolph M. (Yale Western Americana series, 1977)
In the two years after the discovery of gold as Sutter's Mill in 1848, one hundred thousand persons made the difficult trek to California in search of quick wealth. One thousand of them were blacks. By 1860 there were five thousand. They formed the largest voluntary migration of American blacks before the Civil War. Yet few whites then or now have been aware of the part that blacks played in America's epic adventure. Most black Forty-niners went west less to escape a hard lot than to seek their fortune. Some mined alone or together with whites, others formed companies of their own. They included both free blacks and slaves. Lapp examines their life in mining communities and their relationships with other minorities and with whites. He also records for the first time in detail the history of the California Colored Conventions, examining the ideology and eastern origin of its leadership, its problems, and the exodus of many of its members to Canada. Altogether, the author has pieced together a coherent and fascinating narrative of this missing chapter of history. -- from Book Jacket.